The prevalence of alpha-thalassemia amongst Tai and Mon-Khmer ethnic groups residing in northern Thailand: A population-based study - Pathrapol Lithanatudom (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Background: Northern Thailand is one of the highest α-thalassemia incidence areas where 30–40% of inhabitants have been reported to carry aberrant α-globin genes. However, all previous α-thalassemia prevalence surveys in northern Thailand have been undertaken without consideration of ethnicity. Here we report the prevalence of α-thalassemia genes in 4 Tai (Yong, Yuan, Khuen, Lue) and 4 Mon-Khmer speaking populations (Blang, Mon, Paluang, Lawa). Methods: DNA extracted from 141 individuals was genotyped for 4 α-thalassemia deletional types (--SEA, --THAI, -α3.7, -α4.2) using MultiplexGap-PCR analysis and 2 non-deletional types (Hb CS, Hb Pakse) using dot-blot hybridization technique. Results and discussion: A total of 33 α-thalassemia carrying individuals (23.4%) were detected of which 32 were heterozygotes and one was a homozygote. The most common α-thalassemia detected were -α3.7(17.7%) and --SEA(3.5%), while Hb CS was detected in 2.1% of cases. No occurrence of --THAI, -α4.2and Hb Pakse was observed. The prevalence of α-thalassemia carriers varied between the different ethnic groups, with the Yuan having the highest prevalence of α-thalassemia carriers (50%) while the Lawa had the lowest prevalence (0%). The Paluang had a high prevalence (42%) of a single deletion type (-α3.7) possibly related to the endogamous marriage traditions of this ethnic group. Conclusion: The extreme variation of α-thalassemia prevalence among the different ethnic groups highlights the significantly different genetic backgrounds found in these peoples, as consequences of dissimilar cultures. Our study suggests that ethnicity must be considered in any of the disease-causing allele prevalence surveys in this region.